Performance of freshwater sediment microbial fuel cells: Consistency. (23rd February 2016) - Liu, Lihong; Chou, Tzu-Yang; Lee, Chin-Yu; Lee, Duu-Jong; Su, Ay; Lai, Juin-Yih
Abstract: This study experimentally examined the performance consistency of sediment microbial fuel cells (SMFCs) with the same geometry and the same startup protocol. The cells revealed very different characteristics after startup. Doubling the anodic surface area did not enhance the cell performance. Stirring the sediment and aerating the upper water increased voltage output, and the chemical environments (pH and dissolve oxygen concentrations) effectively supported the operation of the studied SMFC. However, individual anodic biofilms and their functions are highly sensitive to extremely small changes in the local environment. The highly inconsistent function of anodic biofilms in SMFCs may hinder their widespread adoption. Highlights: Performance consistency of sediment microbial fuel cells was studied. Cells with same geometry and startup protocol had different characteristics. Anodic biofilms and their functions are sensitive to environment changes. Inconsistent function of anodic biofilms in SMFCs hinders their wide adoption.